Distinct ages and mantle sources for Southern Ocean oceanic plateaus - Peter C. Davidson; Jörg Geldmacher; Yuji Ichiyama; Jia Liu; Folkmar Hauff; Anthony A.P. Koppers; Daniel E. Heaton; Daniel A. Frick; Kaj Hoernle; Odysseas A. Archontikis; Sietske J. Batenburg; Peter Bijl; et al. (Earth and Planetary Science Letters, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Effect of prewarmed crystalloid fluids and an in-line fluid warming device on fluid outflow temperatures at ambient temperatures of 21-22°C and 3.5°C - Lindsay C. Monroe; Jarrod R. Troy; Clark Kogan; Jamie J. Kopper (Journal of Equine Veterinary Science, 2024)

Promoting FAIR Data Through Community-driven Agile Design: the Open Data Commons for Spinal Cord Injury (odc-sci.org) - Abel Torres-Espín; Carlos A. Almeida; Austin Chou; J. Russell Huie; Michael Chiu; Romana Vavrek; Jeff Sacramento; Michael B. Orr; John C. Gensel; Jeffery S. Grethe; Maryann E. Martone; Karim Fouad; et al. (Neuroinformatics, 2022)
The past decade has seen accelerating movement from data protectionism in publishing toward open data sharing to improve reproducibility and translation of biomedical research. Developing data sharing infrastructures to meet these new demands remains a challenge. One model for data sharing involves simply attaching data, irrespective of its type, to publisher websites or general use repositories. However, some argue this creates a ‘data dump’ that does not promote the goals of making data Findable, Accessible, Interoperable and Reusable (FAIR). Specialized data sharing communities offer an alternative model where data are curated by domain experts to make it both open and FAIR. We report on our experiences developing one such data-sharing ecosystem focusing on ‘long-tail’ preclinical data, the Open Data Commons for Spinal Cord Injury (odc-sci.org). ODC-SCI was developed with community-based agile design requirements directly pulled from a series of workshops with multiple stakeholders (researchers, consumers, non-profit funders, governmental agencies, journals, and industry members). ODC-SCI focuses on heterogeneous tabular data collected by preclinical researchers including bio-behaviour, histopathology findings and molecular endpoints. This has led to an example of a specialized neurocommons that is well-embraced by the community it aims to serve. In the present paper, we provide a review of the community-based design template and describe the adoption by the community including a high-level review of current data assets, publicly released datasets, and web analytics. Although odc-sci.org is in its late beta stage of development, it represents a successful example of a specialized data commons that may serve as a model for other fields.

Oviposition Site Selection by the Regal Fritillary, Speyeria idalia, as Affected by Proximity of Violet Host Plants - Brian J. Kopper; Ralph E. Charlton; David C. Margolies (Journal of Insect Behavior, 2000)